(untitled) - Brook-Hart, Guy (Cambridge, 2012)
This course covers all parts of the IELTS exam in detail, providing information, advice and practice to ensure that students are fully prepared for every aspect of the exam. Informed by the Cambridge English Corpus, Complete IELTS includes examples and exercises which tackle key IELTS problem areas, making it the most authoritative IELTS exam preparation course available. Students can choose the level most appropriate to the band they are aiming for.
Keywords: English language,Tiếng Anh; Foreign speakers,Study and teaching,Nói tiếng nước ngoài,Dạy và học